EFNA3 as a predictor of clinical prognosis and immune checkpoint therapy efficacy in patients with lung adenocarcinoma - Mingming Deng; Run Tong; Zhe Zhang; Tao Wang; Chaonan Liang; Xiaoming Zhou; Gang Hou (Cancer Cell International, 2021)
Abstract Background Ephrin receptors (Eph) and their ligands, called ephrins, function in various disease processes. However, the expression level and prognostic value of Eph/ephrins in lung adenocarcinoma (LUAD) are still unclear. Methods The Oncomine and GEPIA databases were used to explore the differential expression of Eph/ephrins in LUAD. Kaplan–Meier plotter was selected to explore the prognostic value of Eph/ephrins. The cBioPortal database was used to analyze the genetic variation of the EFNA3 gene. Immunohistochemistry was used to analyze the expression level and clinical value of ephrin-A3 protein in clinical LUAD tissue. Weighted coexpression network analysis (WGCNA) and gene set enrichment analysis (GSEA) identified the potential regulatory mechanism of EFNA3. CCK-8 assays and colony-forming experiments were used to investigate whether EFNA3 can regulate cell proliferation ability in LUAD. Analysis of lactate, ATP, and glucose uptake levels was used to explore the effect of EFNA3 on glycolysis ability. In addition, we investigated the relationship between EFNA3 and tumor infiltrating immune cells (TIICs). Finally, the potential immunotherapy response prediction value of EFNA3 was also explored. Results In this study, we found that EFNA3 expression was significantly correlated with both overall survival (OS) and progression-free survival (PFS) in LUAD patients based on a comprehensive analysis of the Eph/Ephrin family. Next, the expression of the EFNA3 protein was increased in LUAD tissues and was designated an independent prognostic risk factor. Mechanistically, EFNA3 may be involved in nuclear division, synaptic function, and ion channel activity-related pathways. In vitro experiments confirmed the role of EFNA3 in promoting LUAD cells and showed that it could regulate glycolytic capacity. Moreover, EFNA3 was negatively associated with immunity, stromal infiltration, and several TIICs. Finally, EFNA3 was found to be positively related to multiple immunotherapy biomarkers. Conclusions In conclusion, increased EFNA3 in LUAD patients predicted worse clinical prognosis, promoted LUAD cell proliferation and glycolysis ability, and was related to immunotherapy response.